Ontology-Based Data Warehousing and Mining Approaches in Petroleum Industries - Nimmagadda, Shastri; Dreher, Heinz (Information Science Reference (an imprint of IGI Global), 2007)
Several issues of database organization of petroleum industries have been highlighted. Complex geo-spatial heterogeneous data structures complicate the accessibility and presentation of data in petroleum industries. Objectives of the current research are to integrate the data from different sources and connecting them intelligently. Data warehousing approach supported by ontology, has been described for effective data mining of petroleum data sources. Petroleum ontology framework, narrating the conceptualization of petroleum ontology and methodological architectural views, has been described. Ontology based data warehousing with fine-grained multidimensional data structures, facilitate to mining and visualization of data patterns, trends, and correlations, hiddenunder massive volumes of data. Data structural designs and implementations deduced, through ontology supportive data warehousing approaches, will enable the researchers in commercial organizations, such as, the one of Western Australian petroleum industries, for knowledge mapping and thus interpret knowledge models for making million dollar financial decisions.